State Responsibility in Facing the Pandemic Covid-19 National Disaster - Abid Zamzami (Health Notions, 2021)
The Covid-19 pandemic, which has an impact on the whole world, including Indonesia. Not only does it affect the health aspect, besides that Covid-19 causes considerable material losses. Various aspects were affected, both the socio-culture and the weakening world economy. Of course, this situation cannot be tolerated because it will cause a prolonged crisis. In order to handle it as a rule of law, of course, a legal instrument is needed in the form of statutory regulations. The President has issued various laws and regulations and policie Keywords: state responsibility; health rights